2017
DOI: 10.5935/1981-2965.20170003
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric determination of nitrite in cured meat products

Abstract: _________________________________________________________________________________________________________________Resumo: O mercado de embutidos tem apresentado grande expansão e alta competitividade na última década, uma vez que o consumo de produtos cárneos como salsichas, linguiças e mortadelas tem se tornado cada vez mais presente no hábito alimentar da população brasileira. Sais de cura, como nitrato e nitrito de sódio e de potássio, são largamente utilizados como aditivos alimentares no processamento de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Oliveira et al [15] Brazil Processed meats Brazilian legislation A total of 270 sausage samples from three different manufacturers each were analyzed. The presence of nitrite was in all samples of the meat products analyzed, whose average concentrations ranged from 29.25 ppm to 249.80 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al [15] Brazil Processed meats Brazilian legislation A total of 270 sausage samples from three different manufacturers each were analyzed. The presence of nitrite was in all samples of the meat products analyzed, whose average concentrations ranged from 29.25 ppm to 249.80 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that, at high serum concentrations, nitrite ion forms an irreversible binding with blood hemoglobin, forming methemoglobin. This process hinders the transport of oxygen through fetal tissues, which may lead to fetal growth restriction, causing LBW 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Para o preparo dos extratos, 20 g do pó de espinafre foram misturados com 200 mL de água destilada e mantidos por 2 horas a 90ºC em banho termostático SSD 5L (Solidsteel, Brasil) para extração dos compostos de interesse, seguindo metodologia proposta por Gardes et al, 14 Determinação de pH, conforme método 981.12. 15 Teor residual de nitrito através do método espectrofotométrico descrito por Oliveira et al, 16 em que 10 g de amostra foram quantificadas em um Erlenmeyer e adicionadas de 100 mL de água deionizada a 60 ºC. Em seguida foram acrescentados 5 mL da solução de tetraborato de sódio a 0,5% (m:v) e mantida por 15 minutos sob agitação em banho termostático LUCA-157/28 (Lucadema, Brasil).…”
Section: Preparo E Caracterização Dos Extratos Do Espinafreunclassified